2022
DOI: 10.5194/acp-22-4075-2022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of biomass burning and stratospheric intrusions in the remote South Pacific Ocean troposphere

Abstract: Abstract. The ozone mixing ratio spatiotemporal variability in the pristine South Pacific Ocean is studied, for the first time, using 21-year-long ozone (O3) records from the entire southern tropical and subtropical Pacific between 1994 and 2014. The analysis considered regional O3 vertical observations from ozonesondes, surface carbon monoxide (CO) observations from flasks, and three-dimensional chemistry-transport model simulations of the global troposphere. Two 21-year-long numerical simulations, with and w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 94 publications
0
12
0
Order By: Relevance
“…For the present study, we use the global 3-dimensional chemistry-transport model TM4-ECPL (Daskalakis et al, 2016(Daskalakis et al, , 2022Myriokefalitakis et al, 2016Myriokefalitakis et al, , 2015Kanakidou et al, 2020) driven by ERA-interim reanalysis meteorological fields produced with the European Centre for Medium-Range Weather Forecasts (ECMWF) meteorological model (Dee et al, 2011). The specific model version has a horizontal resolution of 3 o longitude by 2 o latitude with 25 hybrid pressure vertical levels from surface up to 0.1hPa (about 65 km) and uses a model time step of 30 minutes.…”
Section: Global Modellingmentioning
confidence: 99%
“…For the present study, we use the global 3-dimensional chemistry-transport model TM4-ECPL (Daskalakis et al, 2016(Daskalakis et al, , 2022Myriokefalitakis et al, 2016Myriokefalitakis et al, , 2015Kanakidou et al, 2020) driven by ERA-interim reanalysis meteorological fields produced with the European Centre for Medium-Range Weather Forecasts (ECMWF) meteorological model (Dee et al, 2011). The specific model version has a horizontal resolution of 3 o longitude by 2 o latitude with 25 hybrid pressure vertical levels from surface up to 0.1hPa (about 65 km) and uses a model time step of 30 minutes.…”
Section: Global Modellingmentioning
confidence: 99%
“…As noted in the introduction, fine mode particles are known to be long-lived and have been hypothesized by many to dominate maritime CCN budgets. In particular, biomass burning emissions and pollution from South America can result in long-lived fine mode aerosol transport of over nearly 10,000 [2,3,62]. Perhaps emission or physics need to be adjusted in models.…”
Section: Modis-model Comparisonsmentioning
confidence: 99%
“…Similar mid-tropospheric high ozone-low water vapor (HOLW) structures (the term "HOLW" for these structures is coined by Anderson et al (2016)) are repeatedly reported over the major Oceanic regions like Pacific Ocean, Atlantic and Indian Ocean by many researchers during several campaigns. Though a common causative mechanism for the formation of this layer cannot be assigned, as it varies depending on the location, time and background meteorology, several possible pathways are proposed; continental transport (e.g., Boylan et al, 2015), stratospheric intrusions and transport from mid-latitude UT (e.g., Hayashi et al, 2008;Tao et al, 2018;Zachariasse et al, 2000Zachariasse et al, , 2001, transport from biomass burning sites (e.g., Anderson et al, 2016;Taupin et al, 1999) or both stratospheric intrusions and transport from biomass burning locations or continents (e.g., Chatfield et al, 2007;Daskalakis et al, 2022;Weller et al, 1996).…”
Section: 1029/2021jd036412mentioning
confidence: 99%
“…Generally, in the marine region low ozone concentrations are expected due to the lower availability of precursors for production and increased destruction via OH and halogen photochemistry (Kley et al., 1996; Liu et al., 1983; Read et al., 2008; Sarwar et al., 2015). However, continental influence, long‐range transport and prevailing meteorological conditions can significantly affect the ozone distribution over the ocean (e.g., Anderson et al., 2016; Boylan et al., 2015; Daskalakis et al., 2022; Jenkins et al., 2008, 2015; Lelieveld et al., 2001 and references there in). This makes any in situ measurements of ozone over the oceanic region a valuable asset; as the scope of satellite‐borne observations over these regions are limited in their quality of data.…”
Section: Introductionmentioning
confidence: 99%